NGHIÊN CỨU ĂN MÒN THÉP CACBON TRONG MÔI TRƯỜNG KHÍ QUYỂN, ĐẤT VÀ NƯỚC KHU VỰC VEN BIỂN NHA TRANG - Bùi, Bá Xuân; U.I., Kharchenco (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
RESEARCH ON CORROSION OF CARBON STEEL IN AIR, SOIL AND SEA WATER OF NHA TRANG COASTAL AREAResearch results on corrosion in the coastal air, soil and sea water in the weather testing stations in Nha Trang, Viet Nam shows that: the corrosion types of carbon steel in the air is almost uniform. Corrosion rate of the CT-20 steel in the air is the highest and reached 0.74 g/m2.day (after 4 years of testing) in comparison with the corrosion rates of CT-08 and CT-10 steels. The corrosion rate of CT-10 steel in the coastal soil is relatively high, reaching 3.09 g/m2.day (after 10 days), then decreased gradually and stabilized at about 2.52 g/m2.day (after 50 days). In the sea water, the corrosion rate of CT-20 steel reached 3.49 g/m2.day, compared with corrosion rate of 3.00 g/m2.day of CT-08 steel. Corrosion areas on the samples like a shell and a big circle appear under the nest of the died Balanus, and very rarely appear in the case of alive Balanus. Fouling biomass rearched 7.4 to 7.7 kg/m2.